The effect of nursing intervention on self-care self-efficacy and genes related to anxiety in patients with bone marrow transplantation: Self-care self-efficacy in bone marrow transplantation - Xue Wang,; Hongyue Yang,; Xiaoling Zhang,; Qi Fan, (Cellular and Molecular Biology, 2023)
Leukemia patients, after bone marrow transplantation, face many problems that hurt their self-efficacy in self-care. The present study aimed to determine the effect of health promotion strategies on the self-efficacy of patients undergoing bone marrow transplantation in self-care. The expression level of two genes affecting anxiety (i.e., 5-hydroxytryptamine receptor 1A (5-HT1A) and Corticotropin Releasing Hormone Receptor 1 (CRHR1)) was also investigated. For this purpose, this semi-experimental study was conducted before and after in bone marrow transplant candidate patients. Sixty patients were randomly divided into test and control groups. The test group received training on health promotion strategies, and the control group was treated according to the department's routine. Then the self-efficacy of the two groups was compared before and thirty days after the intervention. Also, the expression level of two genes was done by real-time PCR. Data analysis was done using descriptive statistics and paired t-tests, independent t-tests, analysis of covariance, and chi-square in SPSS 11.5 software. The results showed that there was no significant difference between the demographic variables of the two groups. The self-efficacy of the test group in the general scale and dimensions of adaptability, decision-making, and stress reduction increased compared to the control group and themselves before the training (p>0.001). The difference in self-efficacy scores in all dimensions before the intervention was statistically significant (p<0.05). The genetic evaluations also confirmed the obtained results. According to the expression of 5-HT1A and CRHR1 genes, the level of these genes which directly relate to anxiety were significantly decreased after intervention in the test group. In general, teaching health promotion strategies to bone marrow transplant patients can increase the confidence of these patients in taking care of themselves in the treatment process, which will ultimately lead to more survival and a higher quality of life in these patients.